Strengthening Regulations in Protecting Indonesian Migrant Workers Before Departing to The Destination Country of Work - Khairazi, Rifqon (Brawijaya Law Journal, 2021)
So far, there have been many legal problems that have emerged by migrant workers. The issues they face dominated when they work for an employer abroad; most of the cases come from the domestic worker group. This study analyzes the reasons and legal problems that cause Indonesian migrant workers to experience many violations of their rights. This paper's research method is the normative legal method, using legal documents in the form of statutory regulations and several supporting references related to migrant workers. The results showed that the violations that occurred so far were due to many migrant workers who did not get their rights and protection Before Working. In addition, numerous migrant workers departed without going through a departure mechanism following Act No. 18 of 2017. Thus, this article provides suggestions for strengthening regulations regarding migrant workers by amending to the current law and strengthening existing rules through government regulations.